從儒家倫理看克隆人的正當性問題: The Confucian View of Human Cloning - ZHANG, Shunqing (International Journal of Chinese & Comparative Philosophy of Medicine, 2011)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文從儒家倫理的天道基礎和現實基礎兩個角度分析儒家關於克隆人問題的立場與態度。本文認為，論證儒學關於現代生命倫理議題的看法，不應只局限於應用傳統儒學的某種觀點得出某種結論，或樂衷於表面的否定或肯定這樣的判斷。而應該對體現在儒家身上那種對人類生存與命運的強烈憂患意識和人文關懷有一種自覺的體認，這樣才能對儒學關於諸如克隆人這樣的現代生命倫理議題的立場與態度獲得較為全面和深刻的認識。從這樣的觀點出發，本文認為從儒家倫理的天道基礎而言，儒家不會對克隆人的正當性輕率地表示肯定和否定，而是根據具體的情境和目的決定自己的態度，但一般而言，儒家將不會主張克隆人。從儒家倫理的現實基礎來看，儒家對克隆人的態度是鮮明的，那就是認為克隆人缺乏倫理上的正當性，從而反對克隆人。 This essay attempts to offer a Confucian view of human cloning. It analyzes the nature of human cloning from the perspective of Confucian ethics. It argues that we should not make simple “Confucian” conclusions about human cloning based on certainisolated Confucian views, but should take a personal view on the fundamental spirit of Confucianism. Evidently, the foundation of Confucian ethics is its view of the Dao of Heaven (tiendao). From the perspective of this essay, the Dao of Heaven offers twoprinciples with which people should comply. The first principle is that the Dao of humans must follow the Dao of Heaven. That is, people’s activities should not violate the will of Heaven. The second principle is the principle of continuous creation or generation (shengsheng buyi). Such continuous creation or generation is seen as the great virtue (dade) of Heaven. Accordingly, the Dao of Heaven is primarily the method of creation, which characterizes Confucian ethics. This Confucian view of the Dao of Heaven and its two basic principles should be brought to bear on the issue of human cloning in the full sense. By mechanically understanding and applying the principle of generation, it is possible to develop a view of human cloning that grants it legitimacy as a method of reproduction. However, the authentic Confucian sense of generation cannot be understood without the normal relationship between a man and a woman, or specifically, the relationship between husband and wife, which Confucians see as the ultimate starting point of any meaningful human generation. Without the union of husband and wife, human reproduction becomes an unnatural, abnormal event that goes beyond the scope of the Dao of Heaven. That is why Confucianism emphasizes the crucial function of marriage in the normal way of human life. Accordingly, Confucians think that both a father and a mother are necessarily (morally) required to create a normal human child. Techniques such as reproductive human cloning destroy the normal means of human generation and undermine the foundation of Confucian ethics. Confucians cannot accept such techniques. DOWNLOAD HISTORY | This article has been downloaded 185 times in Digital Commons before migrating into this platform.